Laryngeal manifestations of pachyonychia congenita: a clinical case and discussion on management for the otolaryngologist. (20th October 2016) - O'Kane, A M; Jackson, C P; Mahadevan, M; Barber, C
Abstract: Background: Pachyonychia congenita is a rare keratinising disorder, which typically presents during the first three years of life and usually affects the nails and palmoplantar surfaces. It can involve the larynx and potentially result in life-threatening airway obstruction. Methods: A case report is presented and the findings of a literature review are reported. The review involved a PubMed search using the keywords 'pachyonychia congenita' together with 'larynx', 'laryngeal involvement', 'laryngeal obstruction', 'airway obstruction', 'hoarseness' and/or 'stridor'. Results: A five-year-old boy, with confirmed pachyonychia congenita, presented with complications of laryngeal involvement over a four-year period. He required three intubations and a tracheostomy for acute airway obstruction. Treatment with potassium titanyl phosphate laser laryngoscopy stabilised the progression of laryngeal disease. Conclusion: Patients with pachyonychia congenita and laryngeal involvement can have a varied presentation, ranging from hoarseness to acute airway obstruction. Management can be a challenge, requiring early evaluation, regular surveillance and aggressive treatment. This paper reports our experience in managing and treating the laryngeal complications of a child with pachyonychia congenita.